2016
DOI: 10.1037/ipp0000057
|View full text |Cite
|
Sign up to set email alerts
|

Stigma About Mental Illness Among Multidisciplinary Health Care Providers in the Dominican Republic

Abstract: Few studies have examined the attitudes of multidisciplinary health care providers toward mental illness, particularly in Latin America. The present study explored the attitudes of health care providers in the Dominican Republic (DR) toward persons with mental illness. Five Spanish-language focus groups were conducted in different regions of the DR with a purposive sample of 37 multidisciplinary health care providers and administrators. We found that among Dominican health care professionals mental illness was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 35 publications
0
11
0
4
Order By: Relevance
“…However communication between PCC and CMHCs was negatively associated with number of GP visits. This may be because good communication between the team resulted in community mental health professionals assuming some of the functions that would otherwise have been performed by the GP, such as monitoring physical health problems, and this could be because GPs feel unprepared and with low confidence in treating patients with severe mental health problems [ 22 , 23 ], even if it is about their physical health problems. In the CMHU of the Regional Hospital in Malaga specialist mental health care has been coordinated with primary care for more than 20 years.…”
Section: Discussionmentioning
confidence: 99%
“…However communication between PCC and CMHCs was negatively associated with number of GP visits. This may be because good communication between the team resulted in community mental health professionals assuming some of the functions that would otherwise have been performed by the GP, such as monitoring physical health problems, and this could be because GPs feel unprepared and with low confidence in treating patients with severe mental health problems [ 22 , 23 ], even if it is about their physical health problems. In the CMHU of the Regional Hospital in Malaga specialist mental health care has been coordinated with primary care for more than 20 years.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review concluded that older general practitioners (GPs) had a more negative attitude to patients with schizophrenia [10]. It has been shown that GPs’ stigmatisation of patients with mental illness depends on their level of experience of such patients, so that the more experience they have, the less stigmatisation they exhibit [11]. Comparisons of the attitudes of different categories of health professional have shown that GPs stigmatise mental illness more than psychiatrists do [1214].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study carried out in the United States showed that GPs faced significant barriers to providing good care to patients with mental illness: lack of time and resources and lack of confidence [11, 17].…”
Section: Introductionmentioning
confidence: 99%
“…This perception could influence their decisions in daily practice [17], which can be detected by patients [18]. In addition, feeling unprepared, having low confidence, and a lack of resources to manage mental illness from GPs [19,20] could encourage GPs to transfer these patients to specialised care [21]. Both factors could explain the low contact of patients with SRDs with primary care services [16,21,22].…”
Section: Introductionmentioning
confidence: 99%